Cerebrosides from sea cucumber ameliorates cancer-associated cachexia in mice by attenuating adipose atrophy. (August 2015) - Du, Lei; Xu, Jie; Xue, Yong; Takahashi, Koretaro; Xue, Chang-Hu; Wang, Jing-Feng; Wang, Yu-Ming
Highlights: Cerebrosides derived from sea cucumber Acaudina molpadioides (AMC) could ameliorate cancer-associated cachexia (CAC) in mice. AMC rescued CAC in mice by reducing inflammatory cytokines secretion and attenuating adipose atrophy. AMC attenuated adipose atrophy in CAC mice via affecting lipolysis and lipogenesis. Long-chain base (LCB) which is hydrolysed from AMC exhibited more potent anti-tumour effects than AMC. Abstract: Cancer-associated cachexia (CAC) is a multifactorial wasting syndrome which impairs quality of cancer patients' life. Cerebrosides, a principal class of sphingolipids, have various biological actions such as anti-tumour effects. In this study, we found that a continuous oral administration of cerebrosides obtained from sea cucumber Acaudina molpadioides (AMC) at 50 mg/kg body mass per day suppressed body weight loss through alleviating adipose atrophy in CAC mice. The possible mechanism by which dietary AMC prevents adipose atrophy in CAC mice was related to reducing serum inflammatory cytokine levels, regulating over-lipolysis, enhancing the function of lipogenesis and decreasing the lipid over-utilization. To elucidate the structure–activity relationships of AMC and its long-chain base (LCB), we also compared the anti-tumour activities between them. The results indicated that LCB exhibited more prominent anti-tumour effect both in vivo and in vitro . Therefore, AMC and its LCB are highly worth developing as novel agents for cancer therapy.